Study on The Construction of Corporate Negotiation Power Based on Cultural Differences in International Business Negotiations Between The United States and China - Zhao, Shuran (Transactions on Economics, Business and Management Research, 2024)
Traditionally, business negotiation is seen as a face-to-face competition of skills and psychological acumen. However, it can also be viewed as a cultural collision and integration. This paper analyzes three actual business negotiation cases between China and the United States to explore the impact of cultural differences on trade negotiations. The analysis reveals that while cultural differences are inevitable, cultural commonalities can be leveraged. The first case focuses on the pre-negotiation phase, highlighting differing cultural attitudes toward establishing interpersonal relationships. Chinese culture, rooted in collectivism, emphasizes human feelings and interpersonal connections, whereas American culture prefers a direct approach. The second case addresses a common issue in Sino-US negotiations: the challenge of Chinese euphemisms and implicit expressions, which can hinder mutual understanding. The third case examines the power dynamics and identity considerations exhibited by Chinese negotiators. This study concludes that recognizing and understanding cultural differences is crucial in international negotiations. By embracing cultural pluralism, negotiators can develop new strategies and perspectives to enhance negotiating power in Sino-US trade.